Experience of Legal Regulation of Lootboxes in Different Countries: a Comparative Analysis - S. Pour (Journal of Digital Technologies and Law)
Objective: to show how the use of a new business model called Loot boxes, on which modern video games are based, has become a legal problem for jurisdictions in different countries.Methods: drawing on existing literature and contemporary sources, the article explores the potential negative consequences of Loot boxes, provides a comprehensive analysis of existing or proposed regulation, and compares the approaches taken in various national jurisdictions.Results: the article examines the growing concern surrounding the widespread use of a particular form of in-game purchases called Loot boxes. It is strongly criticized on the grounds that Loot boxes are presumed to be a form of gambling within a video game. On this basis, this article argues in favor of their legislative regulation. Having examined the regulatory framework in countries that have already taken action against the use of Loot boxes, such as Belgium, the Netherlands, China, Japan and the Republic of Korea, as well as in countries currently debating their regulation, the author emphasizes the need to adopt consumer protection measures in the gaming industry. This is particularly relevant for vulnerable strata exposed to gambling-related harms. In addition, there is a need to ensure the ethical and responsible use of Loot boxes, as well as to reduce the health and financial risks associated with the use of this business model.Scientific novelty: the paper presents a comparative study of the problems of current or projected social regulation of Loot boxes in video games. The author proposes to seek the solution in a balance between game industry innovations, consumer protection and user well-being, which will ultimately contribute to the creation of a healthier environment for gamers.Practical significance: the study highlights the international scope of the problem the difference in legal and ethical regulatory measures taken in different countries to address the psychological, social and financial consequences associated with the proliferation of lootboxes in video games. These measures are yet to be assessed, taking into account the findings concerning the gaming industry.